Post-traumatic stress disorder - Sarnowska, Marta; Leśków, Anna; Tarnowska, Małgorzata; Wysocki, Andrzej; Pieńkowski, Marek; Rosińczuk, Joanna (Journal of Education, Health and Sport, 2018)
Post-traumatic stress is observed in people who have been directly exposed to traumatic mental and physical stimuli in the form of post-traumatic stress disorder of systemic reactions. Not only soldiers returning from military missions are affected by it, but also victims of all kinds of disasters, rescuers, providing the former with assistance, people pursuing the stress-related professions, including firefighters, paramedics, as well as fans of extreme sports and people, who have experienced unusual situations, such as death of a beloved person, divorce or a traffic accident. The stress symptoms follow the triggering factor. Reaction of the limbic system, associated with the circulation of emotional state, which takes place in the Papez area, causing a variety of vegetative symptoms, especially the circulatory ones, has a vital role to play. The consequences of post-traumatic stress affect both mental and emotional changes, as well as the changes in dynamic stereotype, and they also manifest indirect effects in the family life of an entity and its immediate surrounding. It is important to provide the people affected by post-traumatic stress syndrome with psychological and psychiatric care. The purpose of this article is to review the available literature data on both the post-traumatic stress disorder and its consequences as well as to focus on the key issues related to the prevention and assistance provided for people affected by the syndrome.